The relationship between maternal involvement and self-compassion in parents of children with special needs : Hubungan Keterlibatan Ibu dan Self-compassion pada Orangtua Anak Berkebutuhan Khusus - Mauna, Mauna; PrameswarI, Savira (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2019)
This study aims to look at the relationship between maternal involvement and self-compassion in parentsof children with special needs. Maternal involvement is defined as maternal involvement in aspects of allchild's life seen from two different domains, namely affective and behavior. Self-compassion is the abilityof someone who can give attention and kindness to themselves when facing difficulties in life.Researchers use quantitative methods with a psychological scale. Mother Involvement was measuredusing’s the Nurturance Mothering Scales & Mother Involvement Scale developed by Finley & Schwartz,and the self-compassion was measured by Self-compassion Scale developed by Neff. The sample usedwas 165 people. Sampling uses non probability sampling. Method of data analysis in testing multiplehypotheses using correlation techniques. The results showed a significant relationship between maternalinvolvement with self-compassion with a value of r = 0.041 <p = 0.05, and a significant relationshipbetween maternal involvement reported with self-compassion with a value of r = 0.022 <p = 0 .5. Theresults of the study of the involvement of the desired mother with self-compassion showed no significantrelationship, with a value of p> 0.05.